Monographic study of national and twin pregnancy - Ascenzo Cabello, Jorge (2014)
The term twinning contains many important aspects that constantly occupy the attention of researchers; and affect not only obstetrics and other branches of medicine, such as pediatrics, forensics, etc., but by its vastness, incursions into the field of law and crime, and are a constant concern of biology.